โมเดลเชิงสาเหตุของประสิทธิผลของทีมของชมรมนิสิตนักศึกษาที่มีความฉลาดทางอารมณ์ของกลุ่มเป็นตัวแปรส่งผ่าน : การวิจัยเชิงศึกษาเปรียบเทียบ - ปวีณา คำพุกกะ (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
The purposes of this research were 1) to study the mediating role of the group’s emotional intelligence in studying the effects of the leader’s emotional intelligence on university student clubs’ team effectiveness, 2) to validate of the non-recursive model of university student clubs’ team effectiveness with group’s emotional intelligence as a mediator, 3) to validate the nonrecursive model of university student clubs’ team effectiveness with two variables of group’s emotional intelligence as mediator and 4) to compare the validity between two the above nonrecursive model of university student clubs’ team effectiveness with group’s emotional intelligence as mediator. The research sample consisted of 205 university student clubs, each of which consisted leaders and 3-5 members, with a total sample size of 1,222 from educational institutions nationwide. The research instruments were 2 questionnaires for the heads and member of the university student club. Data were analyzed with descriptive statistics using SPSS 11.5, and the model was validated with an invariance test using LISREL 8.72. The major findings were: 1) group’s emotional intelligence was the mediator variable, mediating the effects of the leader’s emotional intelligence on university student clubs’ team effectiveness (χ² = 53.63, df = 63, p = 0.7939, GFI = 0.96, AGFI = 0.94, RMSEA = 0.0000, RMR = 0.0120, χ²/df = 0.8513), 2) the hypothetical model of university student clubs’ team effectiveness with a mediator fit to the empirical data (χ² = 53.63, df = 63, p = 0.7939, GFI = 0.96, AGFI = 0.94, RMSEA = 0.0000, RMR = 0.0120, χ²/df = 0.8513), 3) the hypothetical model of university student clubs’ team effectiveness with variables fit to the empirical data (χ² = 49.31, df = 60, p = 0.8361, GFI = 0.97, AGFI = 0.94, RMSEA = 0.0000, RMR = 0.0120, χ²/df = 0.8218), and 4) the university student clubs’ team effectiveness with 2 mediators better fit to the empirical (χ²/df = 0.8218) then the one with a mediator (χ²/df = 0.8513) was the second model with 2 mediators.